Retracted: Plastic Solid Waste Management Assessment Among Selected Schools in Gwadabawa Local Government, Sokoto, Nigeria - Gada, Sahabi Nasibatu (EDUMALSYS Journal of Research in Education Management, 2024)
The objective of this work was to assess the plastic solid waste management among selected schools in Gwadabawa Local Government, Sokoto, Nigeria. A descriptive survey (cross-sectional) study was employed and collected data from portions of schools and respondents. The findings indicate that, demographic characteristics of teacher respondents involved in this study are: Males are 66.7%, females are 33.3%; and the levels of education include, NCE/diploma (58.0%), BSc (26.7%), MSc (13.3%), and PhD (2.0%). Regards to students involved, 48.0% are males, 60.0% are females; 36.0% are 18-20 years old, and 64.0% are above 20 years old. The level of education of students include, 60.0% diploma students, and 40.0% certificates students. The effects are listed in the order of frequency as submitted by participants: Release of gases (20.5%), land pollution (17.0%), water pollution (15.0%), attraction of vermin (11.0%), breeding of diseases (10.5%), loss of biodiversity (7.5%), reduction of beauty of environment (7.5%), offensive odour (5.0%), flooding (5.0%), and particulates release (1.0%). Methods of waste elimination are: open disposal occurs among 37.5% schools; likewise, open disposal and burning, occur in 37.5%; while, use as fertilizer was recorded in 12.5% schools. Waste collection methods are either open dumping (80.0%), or use of containers (20.0%). The use of segregation of waste; therewith, only 20.0% practice segregation, the remaining 80.0% do not practice segregation, rather openly display mixtures of waste materials. The possible remedies to mitigate plastic solid waste mismanagement and effects include, education (awareness) and behavior change (53.3%) was mostly stated, funding (26.7%), improvisation (15.3%), scavenging (3.3%), and innovations (1.3%). Policy makers need to act urgently in diverse ways, and the people are supposed to be educated on ways of remediating plastic waste pollution.